2010
DOI: 10.1590/s1516-89132010000500008
|View full text |Cite
|
Sign up to set email alerts
|

Overview of parameters influencing biomass and bioreactor performance used for extracellular ligninase production from Phanerochaete chrysosporium

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…However, only 1,2-dioxygenase (115.7 U/l) and LiP (98.7 U/l) were present in high amounts in the presence of DDT (Table 1). Ntwampe et al (35) reported that the performance of the biomass to produce the required enzymes in liquid cultures was dependent on the presence of readily metabolisable substrates such as glucose. Catalysis of the decomposition of the recalcitrant aromatic compounds in white-rot fungi is affected by extracellular enzymes.…”
Section: Degradation Of Ddt By T Versicolor U97mentioning
confidence: 99%
“…However, only 1,2-dioxygenase (115.7 U/l) and LiP (98.7 U/l) were present in high amounts in the presence of DDT (Table 1). Ntwampe et al (35) reported that the performance of the biomass to produce the required enzymes in liquid cultures was dependent on the presence of readily metabolisable substrates such as glucose. Catalysis of the decomposition of the recalcitrant aromatic compounds in white-rot fungi is affected by extracellular enzymes.…”
Section: Degradation Of Ddt By T Versicolor U97mentioning
confidence: 99%
“…The value of axial dispersion can vary along the reactor bed [24]. ratio L/d must stay above 10 for tubular reactors.…”
Section: Variable Hydrodynamic Influence Reactor Length (L)mentioning
confidence: 99%
“…The samples were collected in sterile plastic bags and stored in a refrigerator (4˚C) prior to use. The WSW was analyzed for its compositions or constituents, while ZD was soaked in warm water, sieved and incubated at 37˚C (24 h) prior to use [6], [20], [21].…”
Section: A Sample Collection and Preparationmentioning
confidence: 99%
“…Phanerochaete chrysosporium BKMF 1767 (ATCC 24725) culture was used for Ligninase production according to the methods described by Ntwampe et al [20]. Lignin peroxidase activity (1 μmol veratryl alcohol oxidized to veratraldehyde per minute) was measured.…”
Section: E Production Of Ligninasesmentioning
confidence: 99%
See 1 more Smart Citation